Mammalian metallothioneins: properties and functions - Babula, Petr; Masarik, Michal; Adam, Vojtech; Eckschlager, Tomas; Stiborova, Marie; Trnkova, Libuse; Skutkova, Helena; Provaznik, Ivo; Hubalek, Jaromir; Kizek, Rene (Metallomics, 2012)
Metallothioneins (MT) are a family of ubiquitous proteins, whose role is still discussed in numerous papers, but their affinity to some metal ions is undisputable. These cysteine-rich proteins are connected with antioxidant activity and protective effects on biomolecules against free radicals, especially reactive oxygen species. In this review, the connection between zinc(II) ions, reactive oxygen species, heavy metal ions and metallothioneins is demonstrated with respect to effect of these proteins on cell proliferation and a possible negative role in resistance to heavy metal-based and non-heavy metal-based drugs.
Keywords: metalothionein; Animals; Drug Resistance, Neoplasm; Metallothionein; proliferace buněk; apoptóza; glutathion; kadmium; Glutathione; Apoptosis; Free Radicals; sekvence aminokyselin; Cadmium; Neoplasms; nádory; Metals; lidé; Molecular Sequence Data; Antineoplastic Agents; protinádorové látky; chemorezistence; kovy; Amino Acid Sequence; Models, Molecular; molekulární sekvence - údaje; molekulární modely; Cell Proliferation; zvířata; volné radikály; Humans